Class II Human Leukocyte Antigen Epitope Mismatch Predicts De Novo Donor‐Specific Antibody Formation After Liver Transplantation. Issue 8 (24th August 2018) - Kubal, Chandrashekhar A.; Mangus, Richard; Ekser, Burcin; Mihaylov, Plamen; Ceballos, Brian; Higgins, Nancy; Chalasani, Naga; Ghabril, Marwan; Nephew, Lauren; Lobashevsky, Andrew
Abstract: Formation of de novo donor‐specific antibodies (dn‐DSAs) has been associated with longterm immunologic complications after liver transplantation (LT). We hypothesized that human leukocyte antigen (HLA) epitope/eplet mismatch (MM) is a marker of immunogenicity and a risk factor for dn‐DSA formation. Sera from 80 LT recipients were prospectively screened for dn‐DSA by a Luminex single‐antigen test (One Lambda, Inc., Canoga Park, CA) at 1, 2, 3, 6, 12, 18, 24, and 36 months after LT. HLA typing of the recipients and donors was performed using polymerase chain reaction (PCR)–SSP and PCR‐SSOP Luminex low‐resolution methods (One Lambda, Inc.). The HLAMatchmaker computer algorithm was used for identification of MM eplets at HLA‐DRB1 and ‐DQA1/B1 loci. Luminex single‐antigen bead solid phase assay was used for antibody analysis. Standard immunosuppression included thymoglobulin‐rituximab induction and tacrolimus maintenance. There were 27 (34%) patients who developed dn‐DSA. There were no episodes of antibody‐mediated rejection, and 9 (11%) developed acute cellular rejection (ACR). A positive crossmatch status and a higher number of HLA‐A, ‐B, ‐DR, and ‐ABDR MMs were not associated with dn‐DSA formation. Patients developing dn‐DSA had a significantly higher number of total (38 ± 2.7 versus 28 ± 2.3; P = 0.01) and antibody‐verified (AbVer; 14 ± 1.1 versus 10 ± 1; P = 0.015) class II MM eplets. By a multivariate regression analysis, the number of class II MM eplets was strongly associated with risk of class II dn‐DSA formation (odds ratio [OR], 1.2; P < 0.01). Patients with ACR had a significantly higher number of total (20.2 ± 1.3 versus 13.9 ± 0.9; P < 0.01) as well as AbVer (10.7 ± 1.1 versus 7.5 ± 0.6; P = 0.03) class I MM eplets. In conclusion, donor‐recipient HLA epitope MM is associated with a risk of dn‐DSA formation and rejection after LT. However, further studies are required to evaluate the clinical utility of epitope matching in LT.